Structural, elastic and mechanical analysis of samarium doped zinc-borosilicate glass - Cheong, Wei Mun; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Fen, Yap Wing; Tee, Tan Sin; Loh, Zhi Wei; Schmid, Siegbert (Elsevier, 2022)
Samarium (III) oxide doped zinc-borosilicate glasses were successfully fabricated using the melt-quenching method by using SLS glass as a source of SiO2. With the progression of Sm3+ concentration, the density of the sample improved from 3.423 g/cm3 to 3.495 g/cm3, while the molar volume raised from 21.760 cm3/mol to 23.665 cm3/mol. The XRD analysis verified the samples’ amorphous nature. Besides, the longitudinal and shear velocity range between 5265.15 and 5706.244 m/s and 2900.247–3039.522 m/s, respectively. The elastic moduli for longitudinal, shear, bulk, and Young’s modulus range between 96.389–111.457 GPa, 29.247–31.624 GPa, 56.493–69.292 GPa, and 75.000–82.345, respectively. Furthermore, with the increment of Sm3+ concentration, the sample’s Poisson’s ratio reduces from 0.302 to 0.270, indicating a progressive rise in cross-link density due to increased glass ionicity. Moreover, the fractal bond connectivity and fugacity rise from 1.826 to 2.170 and 0.060 to 0.083, respectively, with the progression of Sm3+ concentration. The findings imply that the Sm3+ dopant acts as a glass modifier, impacting the elastic performance of the zinc-borosilicate glasses.